KARAKTERISTIK KEBAHASAAN TOKOH LAKI-LAKI DAN PEREMPUAN PADA FILM “TEKA-TEKI TIKA” KARYA ERNEST PRAKASA - Rupidara, Indar; Apriyani, Tristanti (MIMESIS, 2023)
This research focuses on the language features of the male and female characters in the film “Teka Teki Tika” by Ernest Prakasa. The author presents a characteristic description of the language of male and female characters in films based on Lakoff's theory. In this study, the authors used a qualitative descriptive method with careful observation techniques in obtaining data. The purpose of this study is to describe and identify the language features of the male and female characters in the film "Teka Teti Tika" by Ernest Prakasa. The results of the analysis show that there are six linguistic characteristics found in male and female characters based on Lakoff's theory, namely (1) empty adjectives; (2) hedge; (3) intensifier; (4) super polite form; (5) tag question; and (6) avoidance of strong swear word. The most dominant linguistic feature used in this film is the term super polite form where the female character uses the term with the highest frequency compared to the male character.